An approximation to the entropy for quantum decaying states - Civitarese, Enrique Osvaldo (2013)
The concept of entropy was initially defined for systems with thermodynamical equilibrium. We try to extend this notion for quantum non-relativistic decaying states. We use a technique based on path integration on coherent states in order to obtain an approximation to the entropy of a decaying state.